The Influence of Work Environment and Work Discipline During the Dentist Internship Program (PIDGI) on Dentist Performance with Motivation as a Moderating Variable in West Java, Indonesia - Anindita, Sarasti Laksmi; Subyantoro, Arief; Siswanti, Yuni (West Science Business and Management, 2024)
This study examines the impact of the work environment and work discipline during the Dental Internship Program (PIDGI) on dentist performance, moderated by motivation. The research involved 86 respondents who had completed the PIDGI in West Java. Data were collected through a questionnaire using a quantitative research design and analyzed using path coefficient techniques to test the relationships between variables. Motivation was measured using goal-setting theory as the primary indicator. The results of the analysis show that both the work environment and work discipline have a positive and significant effect on dentist performance. Additionally, the study found that motivation positively moderates the relationship between the work environment, work discipline, and dentist performance. This research suggests that a good work environment and high work discipline, when supported by solid motivation, can enhance dentist performance in carrying out their tasks. This research contributes essential knowledge to the enhancement of theory and practice in human resource management in the dental profession, particularly regarding internship programs. The study also recommends improvements in work environment elements and motivation as part of efforts to improve dentist performance.